The Eleventh Doctor : Matt Smith - Smith, Oli (London BBC Children's, 2010)
Who is the eleventh Doctor? How did he get the part? And what's it like stepping into some of the biggest shoes on television? Find out all about Matt Smith's first year as the Doctor, with exclusive interviews about life in the TARDIS, his adventures, co-stars and behind the scenes, as well as all the essential facts about Matt himself! Packed with gorgeous pictures and fascinating facts, as well as a pull-out poster of Matt for your bedroom wall, this is perfect for fans of both the show and Matt himself.
Include Illustrations
Keywords: Smith, Matt (Guitarist)